Carbon Farming as a Tool for Climate Resilience in Smallholder Agriculture - Sadiq, Sanusi Mohammed; Paul Singh, Invinder; Makarfi Ahmad, Muhammad; Sanyinna Sani, Bashir (New Countryside, 2025)
Climate change presents significant challenges to smallholder farmers, whose livelihoods are deeply intertwined with weather patterns, soil health, and overall ecosystem stability. As extreme weather events become more frequent and unpredictable, smallholder agriculture faces increasing risks, including reduced crop yields, soil degradation, and heightened food insecurity. Carbon farming—an approach that integrates agricultural practices designed to sequester carbon dioxide (CO₂) in soil and vegetation—has emerged as a promising strategy to address these challenges. By improving soil organic matter, enhancing biodiversity, and promoting sustainable land use, carbon farming offers a holistic approach to climate resilience. This review explores the potential of carbon farming as a multifaceted solution for climate change mitigation and adaptation in smallholder systems. It draws upon theoretical and conceptual frameworks to assess the effectiveness of carbon farming practices, such as agroforestry, cover cropping, conservation tillage, and biochar application. Additionally, empirical studies demonstrate how these practices improve soil fertility, increase water retention, and reduce greenhouse gas emissions, contributing to both environmental sustainability and food security. However, several challenges hinder widespread adoption, including financial constraints, knowledge gaps, and policy limitations. Addressing these barriers requires targeted interventions, such as capacity-building programs, financial incentives, and supportive policy frameworks. Ultimately, this review underscores the dual benefits of carbon farming: mitigating climate change through carbon sequestration while enhancing smallholder farmers’ adaptive capacities. By integrating carbon farming into agricultural systems, policymakers and stakeholders can foster long-term resilience, ensuring sustainable livelihoods for smallholders while contributing to broader climate goals.